2016
DOI: 10.1016/j.applthermaleng.2016.05.113
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation/boiling heat transfer characteristics in an artery porous structure

Abstract: Abstract:Cryogenic loop heat pipe (CLHP) is one of the key components in the future space infrared 10 exploration system, which enables effective and efficient cryogenic heat transport over a long distance with a 11 flexible thermal link. To realize reliable and long life operation, a CLHP-based thermal control system with 12 redundancy design was proposed in this work, where two nitrogen-charged CLHPs were employed to provide 13 cryocooling at 80-100K. This study focused on the supercritical startup of the CL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 42 publications
(1 reference statement)
0
6
0
Order By: Relevance
“…, Vafaei[30], Dharmendra et al[31], Cooke and Kandlikar[32], Bai et al[33], Wu et al[34], Raveshi et al[35], Shahmoradi et al[36], Ahn et al[37], Hsu and Chen[38], Kwark et al[39], Jun et al…”
mentioning
confidence: 99%
“…, Vafaei[30], Dharmendra et al[31], Cooke and Kandlikar[32], Bai et al[33], Wu et al[34], Raveshi et al[35], Shahmoradi et al[36], Ahn et al[37], Hsu and Chen[38], Kwark et al[39], Jun et al…”
mentioning
confidence: 99%
“…Surface modifications is one of the profound ways to enhance CHF in pool boiling [42]. Surface modification aims to change the surface properties like wettability [30,36,37,46,48,75], porosity [4,39] etc. that influence CHF and BHTC.…”
Section: Introductionmentioning
confidence: 99%
“…Bai et al 30 used a 3-D printing technique to fabricate hybrid channel and sintered coatings. Liter et al 31 fabricate microporous coatings using graphite mold and reported 3.3 times improvement in boiling phase change heat transfer.…”
Section: Introductionmentioning
confidence: 99%